Hit‐Validation Methodologies for Ligands Isolated from DNA‐Encoded Chemical Libraries. (30th January 2017) - Zimmermann, Gunther; Li, Yizhou; Rieder, Ulrike; Mattarella, Martin; Neri, Dario; Scheuermann, Jörg
Abstract: DNA‐encoded chemical libraries (DECLs) are large collections of compounds linked to DNA fragments, serving as amplifiable barcodes, which can be screened on target proteins of interest. In typical DECL selections, preferential binders are identified by high‐throughput DNA sequencing, by comparing their frequency before and after the affinity capture step. Hits identified in this procedure need to be confirmed, by resynthesis and by performing affinity measurements. In this article we present new methods based on hybridization of oligonucleotide conjugates with fluorescently labeled complementary oligonucleotides; these facilitate the determination of affinity constants and kinetic dissociation constants. The experimental procedures were demonstrated with acetazolamide, a binder to carbonic anhydrase IX with a dissociation constant in the nanomolar range. The detection of binding events was compatible not only with fluorescence polarization methodologies, but also with Alphascreen technology and with microscale thermophoresis. Abstract : A multiplexing approach : DNA‐encoded chemical libraries can be screened on target proteins of interest. Hits need to be confirmed by resynthesis and by performing affinity measurements. We present new methods for hit validation, based on hybridization of oligonucleotide conjugates with fluorescently labeled complementary oligonucleotides and on fluorescence anisotropy, Alphascreen, and microscale thermophoresis technology.